Do Postsecondary Internships Address the Four Learning Modes of Experiential Learning Theory? An Exploration through Document Analysis - Stirling, Ashley; Kerr, Gretchen; MacPherson, Ellen; Banwell, Jenessa; Bandealy, Ahad; Battaglia, Anthony (Canadian Journal of Higher Education, 2017)
The educational benefits of embedding hands-on experience in higher education curriculum are widely recognized (Beard & Wilson, 2013). However, to optimize the learning from these opportunities, they need to be grounded in empirical learning theory. The purpose of this study was to examine the characteristics of internships in Ontario colleges and universities, and to assess the congruence between the components of these internships and Kolb’s (1984) experiential learning framework. Information from 44 Ontario universities and colleges, including 369 internship program webpages and 77 internship course outlines, was analyzed. The findings indicated that internship programs overemphasize the practical aspect of the experience at the expense of linking theory and practice. To optimize experiential education opportunities, recommendations include establishing explicit learning activities consistent with each experiential learning mode, including practice, reflection, connecting coursework and practical experience, and implementing creative ideas in practice.